MUSIC BUSINESS FOR MUSIC CREATORS industry mechanics for contemporary creators. - Amos, Jonny ([S.l.] : FOCAL, 2024)
The Music Business for Music Creators is a roadmap to understanding the traditional and emerging income streams that define the modern music industry. It presents the key concepts and principles that underpin the business, with an emphasis on educating and empowering the next generation of music creators to build a career from their creative pursuits. The book provides a comprehensive overview of the mechanics of the music business, from music publishing, marketing and contract negotiation to licensing, streaming and performing. This accessible guide is written with music creators in mind and features case studies, profiles and interviews with established professionals, as well as a glossary of key terms to empower the reader in their understanding of the industry, alongside a number of useful accompanying digital resources. This book is core reading for students of music business and music creation in contemporary music education, and an essential resource for those on music, music production and music performance courses, as well as aspiring and early career professionals.
Keywords: MUSIC / General; MUSIC / Business Aspects; MUSIC / Recording & Reproduction; Music trade -- Vocational guidance; Musicians -- Vocational guidance